O03.4 Modelling intervention strategies for preventing spread of extensively drug resistant gonorrhoea strains among australian MSM. (14th July 2019) - Duan, Qibin; Wood, James; Hui, Ben; Regan, David
Abstract : Background: Recent reports from Australia and the UK of extensively drug resistant (XDR) gonorrhoea strains, have increased concerns over remaining treatment options. Outbreak-type responses to detection of such strains may help to delay wider emergence of such resistance but lack a clear evidence base as to their effect. Here, we use mathematical models to assess the potential impact of outbreak response strategies in a high-incidence population of Australian men who have sex with men (MSM) with gonorrhoea. Methods: We developed an individual-based, anatomical site-specific model of gonorrhoea transmission in Australian MSM. The model was calibrated to available site-specific prevalence and incidence data with respect to the per-act transmission probabilities for four types of sexual practice. As pharyngeal importations were most difficult to control, we focused on these in estimating the probability of elimination of an imported XDR strain. We considered various combinations of contact tracing and screening interventions, with results for each scenario based on 5000 simulations. Results: At current levels of gonorrhoea screening in Australian MSM, we predict persistence of secondary spread at 5 years post-importation in just under 20% of simulations. If all infected regular partners of index patients are traced and treated, this persistence probability declines to ∼8%, and further to ∼4% and 0.04%, respectively, if 20% and 50% of all casual partners in the last two months are traced and treated. Alternatively, If the screening rate is increased to the level recommended in STI management guidelines, the probability of persistence after 5 years is ∼9.7%. When combined with treatment of regular partners, this probability is reduced to <0.01%. Conclusion: This study suggests that contact tracing and screening rate can separately play an important role in responding to outbreaks of XDR gonorrhoea, and in combination these strategies may have the potential to prevent domestic establishment of such strains. Disclosure: No significant relationships.